Trace Elements and Their Effects on Human Health and Diseases - Joseph, Daisy (IntechOpen, 2021)
This book is an excellent compilation of trace elements and their positive and negative effects on human health and the environment. Over two sections, the book examines the adverse effects of trace elements in the human body and the atmosphere and how to overcome them.